Pemberdayaan Masyarakat melalui Pengembangan Desa Wisata - A. Faidlal Rahman (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2011)
Community empowerment is an important sector in developing tourist village. To develop tourist needs to use the resources of the community, as a community, as one of the tourism stakeholders that has an important role to support the achievement of empowered to make them independent. Community empowerment activities, such as a). The meeting, b). Assistance, c). Financial aids, d). Infrastructure building, e). Tourism village organization formation, and f). Mutual assistance, done by the organizer really make the community of Kembang Arum independent in developing tourism village. Keywords: Empowerment, Tourist Village and independence Cole, Stroma, Cultural Tourism Empowerment. In Melanie K. Smith and Mike Robinson, “Cultural Tourism in a Changing World Polities Participation and (Re)Presentation” British; Channel View Publication, 2006